2018 Review of Program Design and Conditionality. (Policy Papers; Policy Paper ;, 2019)
The 2018 Review of Program Design and Conditionality is the first comprehensive stocktaking of Fund lending operations since the global financial crisis. The review assesses program performance between September 2011 and end-2017. Programs during this period were defined by the protracted structural challenges faced by members and hampered by the persistently weak global environment.